Confessions of Shameless Self-Promoters: Great Marketing Gurus Share Their Innovative, Proven, and Low-Cost Marketing Strategies to Maximize Your Success! - Allen Debbie (MC Graw Hill, 2005)
Breakthrough ideas that won’t break the bank—the super-selling secrets behind Chicken Soup and other success stories!